Production of new amilorides as potent inhibitors of mitochondrial respiratory complex I. Issue 7 (3rd July 2015) - Murai, Masatoshi; Habu, Sayako; Murakami, Sonomi; Ito, Takeshi; Miyoshi, Hideto
Abstract: Amilorides, well-known inhibitors of Na + /H + antiporters, have also shown to inhibit bacterial and mitochondrial NADH-quinone oxidoreductase (complex I). Since the membrane subunits ND2, ND4, and ND5 of bovine mitochondrial complex I are homologous to Na + /H + antiporters, amilorides have been thought to bind to any or all of the antiporter-like subunits; however, there is no direct experimental evidence in support of this notion. Photoaffinity labeling is a powerful technique to identify the binding site of amilorides in bovine complex I. Commercially available amilorides such as 5-( N -ethyl- N -isopropyl)amiloride are not suitable as design templates to synthesize photoreactive amilorides because of their low binding affinities to bovine complex I. Thereby, we attempted to modify the structures of commercially available amilorides in order to obtain more potent derivatives. We successfully produced two photoreactive amilorides (PRA1 and PRA2) with a photolabile azido group at opposite ends of the molecule. Graphical abstract: : Amilorides, well-known inhibitors of Na+/H+ antiporters, were reported to inhibit mitochondrial complex I. We attempted to modify the structure of commercially available amilorides and successfully produced two potent photoreactive amilorides.